(untitled) (Al-Qamar, 2020)
Some people, particularly orientalists claim that Prophet Muhammad belonged to a less privileged class; his financial condition was very weak and feeble. They assert that the major monetary source of the Prophet was booty and plunder. Muslim scholars and some of orientalists, on the contrary, affirm that the Prophet belongs to a rich family but he sacrificed his wealth for his sacred mission. This paper discussing the criticism on financial resources of the prophet provides valuable information on the subject. It concludes that the Prophet could create wealth and could lead a lavish life, but he did not live this way for the sake of others. The prophetic economy was actually the reflection of the Islamic principle of moderation, contentment and trust in God. His life was a symbol of gratitude with the enjoyment of the blessings created by Allah Almighty within the limitations of the principles of Sharīʻah.